2016
DOI: 10.1002/hed.24609
|View full text |Cite
|
Sign up to set email alerts
|

Osseointegrated implants into a variety of composite free flaps: A comparative analysis

Abstract: Implants placed into VBGs have a reasonable success rate in well-selected patients. © 2016 Wiley Periodicals, Inc. Head Neck 39: 443-447, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
61
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(64 citation statements)
references
References 18 publications
1
61
1
1
Order By: Relevance
“…Ideally mandibular reconstruction should be accompanied by immediate or delay dental implantation to optimize mastication, being the ultimate goal in oromandibular reconstruction. FFFs had historically shown more reliability for osseointegrated implantation, with a superior bone stock (Burgess, Leung, Chellapah, Clark, & Batstone, ); however, multiple investigators have demonstrated that scapular system flaps are implantable (Tang, Bearelly, & Mannion, ). Many head and neck cancer patients are poor candidates for dental implantation due to radiotherapy, poor dental hygiene, lower socioeconomic status, and trismus (Dholam, Pusalkar, Yadav, Quazi, & Somani, ) among other factors resulting in a very small portion of our population being rehabilitated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ideally mandibular reconstruction should be accompanied by immediate or delay dental implantation to optimize mastication, being the ultimate goal in oromandibular reconstruction. FFFs had historically shown more reliability for osseointegrated implantation, with a superior bone stock (Burgess, Leung, Chellapah, Clark, & Batstone, ); however, multiple investigators have demonstrated that scapular system flaps are implantable (Tang, Bearelly, & Mannion, ). Many head and neck cancer patients are poor candidates for dental implantation due to radiotherapy, poor dental hygiene, lower socioeconomic status, and trismus (Dholam, Pusalkar, Yadav, Quazi, & Somani, ) among other factors resulting in a very small portion of our population being rehabilitated.…”
Section: Discussionmentioning
confidence: 99%
“…Ideally mandibular reconstruction should be accompanied by immediate or delay dental implantation to optimize mastication, being the ultimate goal in oromandibular reconstruction. FFFs had historically shown more reliability for osseointegrated implantation, with a superior bone stock (Burgess, Leung, Chellapah, Clark, & Batstone, 2017); however, multiple investigators have demonstrated that scapular system flaps are implantable (Tang, Bearelly, & Mannion, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Many retrospective clinical studies have supported this hypothesis, [10][11][12] whereas others have shown no statistical difference in implant survival between irradiated and nonirradiated bone. 2,13,14 In this study, we aimed to report the success rate of both dental and craniofacial osseointegrated implants in patients with head and neck cancer. Furthermore, we aimed to define the impact of radiotherapy, smoking, and chemotherapy on the success and failure of these implants.…”
Section: Introductionmentioning
confidence: 99%
“…Placement of the bone in a position that is not suitable for dental rehabilitation is an all too frequent outcome, if some basic principles are not followed. Previous research in this area has focussed on osseointegration into the fibula free flap which is the most widely used donor site for mandibular reconstruction but all osseous free flaps of sufficient bone volume are capable of highly reliable osseointegration (Fig. ).…”
Section: Contemporary Practicementioning
confidence: 99%
“…). Predictable long term prosthetic success is achievable, although there are many studies which demonstrate the impaired survival of osseointegrated implants in the irradiated patient . In addition, as the implant must pass through skin or altered mucosa rather than normal gingiva peri‐implant mucositis and peri‐implantitis are challenges for all the rehabilitation team to manage.…”
Section: Contemporary Practicementioning
confidence: 99%